2010
DOI: 10.4269/ajtmh.2010.09-0061
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ultrasonography to Evaluate Schistosoma japonicum-Related Morbidity in Children, Sichuan Province, China, 2000–2007

Abstract: Abstract. Liver ultrasonography is a convenient way to evaluate Schistosoma japonicum -related morbidity; however, no consensus standards exist, and data on use in Chinese children are scant. We describe 7 years of ultrasound findings in a prospective cohort of 151 children from an endemic area in Sichuan Province, China and evaluate technical aspects of the ultrasound methodology. Although prevalence of infection decreased over time, prevalence of hepatomegaly increased, which was likely caused by re-infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Generalized estimating equations logistic regression with exchangeable correlation was used for all other measures. doi:10.1371/journal.pntd.0000685.t004 measures has been shown to be poor in a pediatric population, and further efforts to evaluate the accuracy of organ and vein size measurements are needed [19].…”
Section: Discussionmentioning
confidence: 99%
“…Generalized estimating equations logistic regression with exchangeable correlation was used for all other measures. doi:10.1371/journal.pntd.0000685.t004 measures has been shown to be poor in a pediatric population, and further efforts to evaluate the accuracy of organ and vein size measurements are needed [19].…”
Section: Discussionmentioning
confidence: 99%
“…29,30 It includes assessment of expected morbidities such as splenomegaly and left lobe hepatomegaly, as well as successively more pronounced liver ultrasound changes scored as image patterns (IP) A (normal), B ("starry sky," abnormal linear opacities of unclear significance), and C through F (progressive hepatic fibrosis). These characteristic, partially reversible 31,32 schistosomiasis-associated abnormalities in adults have also been found in school-aged children, 33,34 but morbidity in PSAC using this system or ultrasound more generally is again not well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of this sensitization on fibrosis-related outcomes as these infants acquire natural infections remains unknown. Multiple studies have shown that hepatomegaly and fibrosis associated with schistosome infection continue to affect children and adults even after initial infection is resolved (30)(31)(32). Because fibrosis is a morbidity associated with chronic schistosome infection, it is relatively rare in children (30,33,34); however, we speculate that the risk of developing schistosome-associated fibrosis following acquisition of infection may differ in individuals who were sensitized in utero to respond to schistosome antigens with a profibrotic signature.…”
Section: Discussionmentioning
confidence: 56%